Early Detection of Primary Open Angle Glaucoma Using Optical Coherence Tomographic Ganglion Cell Layer Thickness - Aqsa Saleem, Syed Ahmad Hassan Waqas Subzwari, Syed Shujaat Ali Shah, Saira Bano, Hamna Iqbal, Sareen Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: POAG is a leading cause of blindness worldwide. Early detection is key to preventing progression, however, traditional diagnostic methods are not able to detect the disease at the early stages. An emerging tool for early diagnosis is optical coherence tomography (OCT) for quantifying the thinning of the retinal ganglion cell layer (GCL) which precedes functional loss. Methodology: This prospective, observational study was performed for one year in a tertiary eye care center in Faisalabad, Pakistan from January 2022 to January 2023. There was n=50 patients with early POAG and 50 age and sex matched healthy controls enrolled, for a total of n=100 subjects (200 eyes). An ophthalmic examination, including measurement of intraocular pressure (IOP), standard automated perimetry (SAP), and spectral domain OCT imaging, was performed comprehensively. A 6 × 6 mm² macular cube scan centered on the fovea was acquired using OCT, and automated segmentation algorithms calculated the average, superior, and inferior GCL thickness. Clinical parameters and OCT measurements were compared between the groups, and correlations between GCL thickness and visual field indices were assessed using statistical analyses performed using SPSS. Results: IOP and MD in POAG patients were significantly higher than in healthy controls (p < 0.001). The thickness of the GCL in POAG patients was significantly reduced in the average, superior, and inferior sectors from controls (p < 0.001). Decreased GCL thickness was linearly correlated (r = -0.65, p < 0.001) to worsening MD in the POAG group. Conclusion: Measurements of the ganglion cell layer by OCT are sensitive and objective biomarkers for the early detection of POAG. POAG patients have significantly smaller GCL thickness and there is strong correlation with functional deficits which makes it an ideal candidate for early glaucoma screening in resource-poor settings such as Pakistan, as OCT can be integrated in early screening protocols. Keywords: Primary Open-Angle Glaucoma, Optical Coherence Tomography, Ganglion Cell Layer, Early Detection, Visual Field, Faisalabad, Pakistan